Formal and Informal Communication Strategies in Employee Union Participation: Strategi Komunikasi Formal dan Informal dalam Partisipasi Serikat Pekerja - Mulyono; Ainur Rochmaniah (Academia Open, 2025)
General Background: Labor unions advocate workers’ rights and welfare through structured communication and socialization activities that foster awareness and collective engagement. Specific Background: At PT Indal Steel Pipe, Gresik Regency, the labor union conducts socialization programs to encourage employee participation despite relatively low membership involvement. Knowledge Gap: Empirical insight remains limited regarding integrated organizational communication approaches used by company-based labor unions to address participation barriers. Aims: This study examines communication strategies applied by the labor union to promote unionization among employees. Results: Using a qualitative case study with interviews, observations, and documentation, the findings show that the union implements formal socialization through structured education and informal engagement through interpersonal and persuasive dialogue, supported by written, oral, and electronic communication channels. Transparency, management support, and employee trust support participation, while scheduling conflicts, apathy, stigma, and individualistic workplace culture remain challenges. These barriers are addressed through unit-based representatives and digital communication platforms. Novelty: The study presents an integrated model combining macro and micro organizational communication networks with formal and informal approaches in an industrial union context. Implications: The findings offer guidance for strengthening union communication capacity and organizational literacy to support sustainable employee participation in collective representation. Highlights: Structured Socialization and Interpersonal Dialogue Form Complementary Engagement Mechanisms. Transparency, Managerial Support, and Trust Facilitate Membership Involvement. Scheduling Conflicts, Stigma Concerns, and Individualistic Workplace Culture Restrict Organizational Engagement. Keywords: Labor Union Communication, Unionization Socialization, Employee Participation, Organizational Communication Networks, Digital Internal Media